2004
DOI: 10.1016/j.jcrs.2004.02.085
|View full text |Cite
|
Sign up to set email alerts
|

Posterior capsule opacification in rabbit eyes implanted with hydrophilic acrylic intraocular lenses with enhanced square edge

Abstract: The square optic edge is the most important IOL design feature for PCO prevention. However, it should be present for 360 degrees around the IOL optic to provide an effective barrier effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 8 publications
2
60
0
3
Order By: Relevance
“…Rabbit and clinical studies found a better barrier effect against lens epithelial cell (LEC) migration with this design than with the earlier version (model 570H) with a smooth optic-haptic transition. 6,[21][22][23] The study IOL evaluated in our study has loops that are thinner close to the optic-haptic junctions, creating beveled barrier steps anteriorly and posteriorly to enhance prevention of cell migration/proliferation toward the visual axis. Even though PCO started at the level of the optic-haptic junctions in 3 of 5 eyes with the study IOL (versus 4 of 5 control eyes), significantly less PCO was observed in the study eyes at the end of the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rabbit and clinical studies found a better barrier effect against lens epithelial cell (LEC) migration with this design than with the earlier version (model 570H) with a smooth optic-haptic transition. 6,[21][22][23] The study IOL evaluated in our study has loops that are thinner close to the optic-haptic junctions, creating beveled barrier steps anteriorly and posteriorly to enhance prevention of cell migration/proliferation toward the visual axis. Even though PCO started at the level of the optic-haptic junctions in 3 of 5 eyes with the study IOL (versus 4 of 5 control eyes), significantly less PCO was observed in the study eyes at the end of the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia, surgical preparation, and bilateral phacoemulsification with IOL implantation were performed as described in previous studies. [4][5][6]14 Briefly, a fornix-based conjunctival flap was fashioned. A corneoscleral incision was then made using a crescent blade, and the anterior chamber was entered with a 3.0 mm keratome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diferentemente de Werner et al (2004) e Awasthi et al (2009), que sugerem que as diversas técnicas existentes, com diferentes graus de sucesso, tendem a diminuir a OCP, neste estudo, no M24, a utilização do tratamento à base de plasma de polietilenoglicol e flúor não promoveu a redução ou diminuição da OCP.…”
Section: Resultsunclassified
“…However, studies suggest that square-edged IOLs should completely encompass the 360 degrees around the IOL optic in order to provide an effective barrier (25) . Furthermore, another study has shown differences between brands of square-edged len- ses, and suggested that variations in their edge profiles may account for clinical differences in postoperative PCO rates (26) .…”
Section: Discussionmentioning
confidence: 99%